Nonvariceal Upper Gastrointestinal Bleeding: What an Interventional Radiologist Should Know - Baby, Akhil; Singh, Shobhit; Betgeri, Somsharan; Philips, Cyriac Abby; Augustine, Philip; Sasidharan, Rajesh (Digestive Disease Interventions, 2024)
Acute nonvariceal upper gastrointestinal bleeding (NVUGIB) is a common medical emergency associated with significant morbidity and mortality. The most common cause of NVUGIB is peptic ulcer disease, but the differential diagnosis is diverse. The management of NVUGIB begins with resuscitation of the patient followed by early upper gastrointestinal (GI) endoscopy for diagnosis and initial treatment. Endovascular interventions have largely replaced surgery for the cases where endoscopic therapy fails, reflecting a paradigm shift toward minimally invasive and effective management strategies. It is essential to have a comprehensive understanding of arterial anatomy, common vascular variations, and different collateral pathways for successful endovascular management of NVUGIB. This review provides a thorough overview of NVUGIB, encompassing the management algorithm, imaging protocol, anatomical considerations, embolization techniques, types of embolic agents, and potential complications that interventional radiologists should consider when managing cases of NVUGIB.
Keywords: pancreaticoduodenal; Amplatzer; empirical